Swine Dendritic Cell Response to Porcine Reproductive and Respiratory Syndrome Virus: An Update - Hernández, Jesús; Li, Yanli; Mateu, Enric (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are the most potent antigen-presenting cells, unique to initiate and coordinate the adaptive immune response. In pigs, conventional DCs (cDCs), plasmacytoid DCs (pDCs), and monocyte-derived DCs (moDCs) have been described in blood and tissues. Different pathogens, such as viruses, could infect these cells, and in some cases, compromise their response. The understanding of the interaction between DCs and viruses is critical to comprehend viral immunopathological responses. Porcine reproductive and respiratory syndrome virus (PRRSV) is the most important respiratory pathogen in the global pig population. Different reports support the notion that this virus can modulate pig immune response in addition to their genetic and antigenic variability. The present review briefly summarizes and discusses the previous studies on the interaction of in vitro derived bone marrow (bm)- and monocyte (mo)- DCs, and in vivo isolated cDCs, pDCs, and moDCs with PRRSV1 & 2.